A facile strategy for fabricating multifunctional ionogel based electronic skin. Issue 25 (18th June 2020) - Sun, Jingxian; Li, Ruiqi; Lu, Guoqiang; Yuan, Yixin; Zhu, Xiaoqun; Nie, Jun
Abstract : A multifunctional ionogel based electronic skin was synthesized via a facile strategy. Abstract : Electronic skins (e-skins) have attracted increasing research interest in recent years, owing to their tremendous potential application in artificial intelligence. Nevertheless, the scarce functionality and complex manufacturing process still severely hinder their application. Meanwhile, how to integrate various sensing capabilities into a single sensor is still an urgent problem. In this study, a novel ionogel e-skin was fabricated by a very facile strategy, polymerizing acrylic acid (AA) in ionic liquid 1-ethyl-3-methylimidazolium chloride ([EMIM]Cl). The obtained e-skin exhibited super functions, including excellent transparency, superior stretchability, extreme temperature tolerance and outstanding self-adhesion. The e-skin demonstrated reasonably high sensitivity to various external stimuli, including strain and temperature. It is believed that this study provides a novel and facile approach to fabricate high-performance bimodal e-skin for wearable electronics, biomedical devices, and soft robotics.